2007
DOI: 10.1088/1751-8113/40/31/008
|View full text |Cite
|
Sign up to set email alerts
|

Background activity drives criticality of neuronal avalanches

Abstract: We establish a general framework that explains how leaky, dissipative systems, such as neuronal networks (NN), can exhibit robust self-organized criticality (SOC). Consistent with recent experiments, we propose that persistent membrane potential fluctuations allow NNs to transform from a sub-critical to a critical state. Our results also account for the tendency in small networks to tip towards an epileptiform state (the case of largely synchronized neurons) when background activity is strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…One class of models, based on self‐organized criticality (SOC) [ Hergarten and Neugebauer , 1998; Piegari et al , 2006], hint at some possible mechanisms yielding the observed statistics. SOC is a theory underlying the spontaneous emergence of critical‐like behavior (i.e., power laws and critical exponents) in systems for which the timescales between buildup and release of stress are separated, and for which the stress‐transfer mechanism is generally nonconservative [ Juanico et al , 2007a, 2007b; Juanico and Monterola , 2007]. SOC concepts have aroused great interest in the study of granular matter [ Jaeger et al , 1989], a well‐known example of which is the ricepile experiment [ Frette et al , 1996].…”
Section: Introductionmentioning
confidence: 99%
“…One class of models, based on self‐organized criticality (SOC) [ Hergarten and Neugebauer , 1998; Piegari et al , 2006], hint at some possible mechanisms yielding the observed statistics. SOC is a theory underlying the spontaneous emergence of critical‐like behavior (i.e., power laws and critical exponents) in systems for which the timescales between buildup and release of stress are separated, and for which the stress‐transfer mechanism is generally nonconservative [ Juanico et al , 2007a, 2007b; Juanico and Monterola , 2007]. SOC concepts have aroused great interest in the study of granular matter [ Jaeger et al , 1989], a well‐known example of which is the ricepile experiment [ Frette et al , 1996].…”
Section: Introductionmentioning
confidence: 99%
“…We study Bak-TangWiesenfeld sandpile dynamics (23,24) on networks derived from real, interdependent power grids and on sparsely coupled, random regular graphs that approximate the real topologies. Sandpile dynamics are paradigms for the cascades of load, self-organized criticality, and power law distributions of event sizes that pervade disciplines, from neuronal avalanches (25)(26)(27) to cascades among banks (28) to earthquakes (29), landslides (30), forest fires (31,32), solar flares (33,34), and electrical blackouts (15). Sandpile cascades have been extensively studied on isolated networks (35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…Many complex systems affecting modern life, from infrastructure systems like power grids to the natural catastrophes that threaten them, appear to be poised near criticality. For instance, power law distributions seem to characterize the sizes of electrical blackouts [1], financial fluctuations [2], neuronal avalanches [3][4][5], earthquakes [6], landslides [7], overspill in water reservoirs [8], forest fires [9,10] and solar flares [11,12]. Since its introduction in 1987 [13,14], the Bak-Tang-Wiesenfeld (BTW) sandpile has served as a useful paradigm for the self-organizing dynamics that may drive these systems toward critical points (also called self-organized criticality or SOC).…”
Section: Introductionmentioning
confidence: 99%